Smoking influence in Takotsubo syndrome: insights from an international cohort - Núñez-Gil, Iván J.; Santoro, Francesco; Vazirani, Ravi; Novo, Giuseppina; Blanco-Ponce, Emilia; Arcari, Luca; Uribarri, Aitor; Cacciotti, Luca; Guerra, Federico; Salamanca, Jorge; Musumeci, Beatrice; Vedia, Oscar; et al. (Frontiers in Cardiovascular Medicine, 2023)
Aims To assess the influence of tobacco on acute and long-term outcomes in Takotsubo syndrome (TTS). Methods Patients with TTS from the international multicenter German Italian Spanish Takotsubo registry (GEIST) were analyzed. Comparisons between groups were performed within the overall cohort, and an adjusted analysis with 1:1 propensity score matching was conducted. Results Out of 3,152 patients with TTS, 534 (17%) were current smokers. Smoker TTS patients were younger (63 ± 11 vs. 72 ± 11 years, p < 0.001), less frequently women (78% vs. 90%, p < 0.001), and had a lower prevalence of hypertension (59% vs. 69%, p < 0.01) and diabetes mellitus (16% vs. 20%, p = 0.04), but had a higher prevalence of pulmonary (21% vs. 15%, p < 0.01) and/or psychiatric diseases (17% vs. 12%, p < 0.01). On multivariable analysis, age less than 65 years [OR 3.85, 95% CI (2.86–5)], male gender [OR 2.52, 95% CI (1.75–3.64)], history of pulmonary disease [OR 2.56, 95% CI (1.81–3.61)], coronary artery disease [OR 2.35, 95% CI (1.60–3.46)], and non-apical ballooning form [OR 1.47, 95% CI (1.02–2.13)] were associated with smoking status. Propensity score matching (PSM) 1:1 yielded 329 patients from each group. Smokers had a similar rate of in-hospital complications but longer in-hospital stays (10 vs. 9 days, p = 0.01). During long-term follow-up, there were no differences in mortality rates between smokers and non-smokers (5.6% vs. 6.9% yearly in the overall, p = 0.02, and 6.6%, vs. 7.2% yearly in the matched cohort, p = 0.97). Conclusions Our findings suggest that smoking may influence the clinical presentation and course of TTS with longer in-hospital stays, but does not independently impact mortality.